Особливості та шляхи реалізації функції оборони держави - Щербюк, Н.; Щербюк, М.; Shcherbiuk, N.; Shcherbiuk, M. (Східноєвропейський національний університет імені Лесі Українки, 2015)
Стаття присвячена дослідженню функції оборони країни. Функції держави встановлюються залежно від основних завдань, які стоять перед ним на тому чи іншому етапі його розвитку. В умовах загострення глобальних проблем людства, порушення світового правопорядку Російською федерацією, що зумовило анексію Криму, проведення АТО в Донецькій і Луганській областях, особливої актуальності набувають проблеми реалізації вищевказаної зовнішньої функції нашої держави. Авторами проаналізовані позиції вчених із зазначеної проблеми, положення законодавства у цій сфері. У статті наголошується, що діяльність держави щодо забезпечення свого захисту має складний зміст і різні цілі. На їх реалізацію спрямовані підготовка та ведення політичної, дипломатичної, інформаційної та економічної боротьби. Невід'ємною складовою частиною цієї діяльності є створення військової організації держави і здійснення керівництва нею. На основі проведених досліджень визначено особливості функції оборони держави та шляхи її реалізації в сучасних умовах. The article deals with one of the external functions of the state – the function of the defense of a country. The functions of the state are set depending on the major objectives facing the state at this or that stage of its development. In the conditions of aggravation of global problems of humanity violation of the international legal order by Russian Federation that caused he annexation of the Crimea, conducting ATO in the Donetsk and Lugansk regions, problems of implementation of the above-mentioned external function of our state have become particularly important and urgent. The authors analyze the scientists’ approaches to the above-mentioned problem and legislative provisions in this area. It has been proved that activities of the state to ensure its protection has a complex meaning and different objectives. Preparation and maintenance of the political, diplomatic, informational and economic struggle are aimed at realization of these objectives. An integral part of this activity is the creation of the state military organization and providing management of it. The authors state that each function of the state is carried out simultaneously in both legal and organizational forms, including the function of defense of a country. The results of the study helped to identify the peculiarities of the function of defense of the state and the ways of its realization in modern conditions.
Features and Ways of Realization of the Defense Function of a State
Keywords: держава; функції держави; внутрішні і зовнішні функції держави; суверенітет; військові формування; state; functions of a state; external and internal functions of a state; sovereignty; military forces